Air layering in cassia (Cinnamomum aromaticum Nees.) - REMA, B KRISHNAMOORTHY, J (Journal of Spices and Aromatic Crops, 1994)
Air layering in 2 year old cassia plants (Cinnamomum aromaticum) is reported for the first time. A success of 87.5 and 50.0% rooting was obtained when carried out during July and November, respectively, with 100% field establishment.